110 Evaluation of High-Protein Diets Differing in Protein Source in Healthy Adult Dogs. (21st September 2022) - Sieja, Kelly M; Oba, Patrícia M; Kelly, Janelle; Swanson, Kelly S
Abstract: Given the dynamic market for protein-based ingredients in the pet food industry, demand continues to increase for both plant- and animal-based options. Animal and plant protein sources contain different amino acid profiles and vary in digestibility, which can affect the protein quality provided to the animal. Our objective was to evaluate the apparent total tract digestibility (ATTD) and compare protein quality of canine diets differing in protein source using healthy adult dogs. Four isocaloric and isonitrogenous, extruded diets were formulated to meet all AAFCO nutrient recommendations for adult dogs, with the primary difference being protein source: 1) chicken by-product meal (CBPM), 2) deboned chicken, dried chicken, and spray dried chicken (DC), 3) corn gluten meal (CGM), or 4) wheat gluten meal (WGM). Adult female beagles (n = 20; BW = 9.9 kg; age = 6.3 yr) were used in a replicated 4×4 Latin square design (n=12/treatment). Each period consisted of a 22-d adaptation phase, 5 d for total and fresh fecal collection, and 1 d for blood collection. All data were analyzed using the Mixed Models procedure of SAS 9.4. Diets contained similar crude protein (CP) concentrations (39.8%-41.7%), but DC had the most balanced AA profile (indispensable AA:dispensable AA ratio). Fecal scores were greater (P< 0.01) in dogs fed DC or CBPM than those fed WGM or CGM, but all remained within an appropriate range. Apparent dry matter digestibility was less (P< 0.0001) in dogs fed CBPM or CGM than those fed DC or WGM. Dogs fed CBPM had decreased (P< 0.0001) apparent organic matter, CP, and energy digestibilities than those fed the other 3 diets. Apparent CP digestibility was also reduced (P< 0.0001) in dogs fed DC or CGM than those fed WGM. Considering AA profiles and digestibility data together, the DC diet clearly provided the most and greatest quality protein of all diets tested.